2002
DOI: 10.1016/s0021-9673(01)01507-2
|View full text |Cite
|
Sign up to set email alerts
|

Determination of trace level bromate and perchlorate in drinking water by ion chromatography with an evaporative preconcentration technique

Abstract: A simple sample preconcentration technique employing microwave-based evaporation for the determination of trace level bromate and perchlorate in drinking water with ion chromatography is presented. With a hydrophilic anion-exchange column and a sodium hydroxide eluent in linear gradient, bromate and perchlorate can be determined in one injection within 35 min. Prior to ion chromatographic analysis, the drinking water sample was treated with an OnGuard-Ag cartridge to remove the superfluous chloride and concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 20 publications
(12 reference statements)
0
15
0
Order By: Relevance
“…As there are lots of fireworks produced and set off in most regions in China, there could be perchlorate pollution in China. Liu (Liu et al, 2002;Liu et al, 2003) et al detected perchlorate in water in several water plants. Nevertheless, there is no extensive research on the occurrence of perchlorate in China.…”
Section: Introductionmentioning
confidence: 99%
“…As there are lots of fireworks produced and set off in most regions in China, there could be perchlorate pollution in China. Liu (Liu et al, 2002;Liu et al, 2003) et al detected perchlorate in water in several water plants. Nevertheless, there is no extensive research on the occurrence of perchlorate in China.…”
Section: Introductionmentioning
confidence: 99%
“…In order to accurately detect the concentration of the compounds, the sample should be concentrated prior to analysis. The microwave-based evaporative concentration technique has been proved a convenient and effective method for the pretreatment of some thermally stable inorganic compounds in drinking water (Liu et al, 2002). In this section, the boiling points of MCAA, DCAA and TCAA are all above 100°C.…”
Section: Sample Pretreatmentmentioning
confidence: 98%
“…In China, there is no official legislation on the MCLs of DBPs in drinking water, and few data on the research of this area were reported (Li et al, 2001;Liu et al, 2002). In this paper, according the regulation of DBPs in drinking water of WHO, bromate and three chloroacetic acids in bottled drinking water samples commercially available in Beijing were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The method is free of interferences from common inorganic anions; presented quantitative recoveries at µg l -1 and the MDL of 150 ng l -1 permits quantification of perchlorate below the levels that ensure adequate health protection. Liu et al (2002) proposed a new method of determining trace level of bromate and perchlorate in drinking water by IC with an evaporative preconcentration technique. Due to the fact that concentrations of bromate and perchlorate in drinking water are very low and large amounts of chloride can interfere with the determination of bromate, they proposed that, prior IC analysis, the drinking water was treated with an OnGuard-Ag cartridge to remove the superfluous chloride and concentrated 20-fold using a PTFE beaker in a domestic microwave oven for 15 minutes.…”
Section: Perchloratementioning
confidence: 99%